2011
DOI: 10.1210/edrv.32.1.zef152a
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Expression in the Caput Epididymal Epithelium Is Essential for Development of the Initial Segment and Epididymal Spermatozoa Transit

Abstract: Naϩ /I Ϫ symporter (NIS)-mediated iodide uptake into thyroid follicular cells serves as the basis of radioiodine therapy for thyroid cancer. NIS protein is also expressed in the majority of breast tumors, raising potential for radionuclide therapy of breast cancer. KT5823, a staurosporine-related protein kinase inhibitor, has been shown to increase thyroid-stimulating hormone-induced NIS expression, and thus iodide uptake, in thyroid cells. In this study, we found that KT5823 does not increase but decreases io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 0 publications
4
15
0
Order By: Relevance
“…Interestingly, another RNF8-dependent escape gene, Ar (androgen receptor), is also significantly down-regulated in Rnf8-KO mice. The expression of Ar is crucial for maturation of spermatozoa within the epididymis in mice (O'Hara et al 2011). Moreover, a cohort study of infertile men showed that mutations of AR affect sperm motility and counts in humans (Lazaros et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, another RNF8-dependent escape gene, Ar (androgen receptor), is also significantly down-regulated in Rnf8-KO mice. The expression of Ar is crucial for maturation of spermatozoa within the epididymis in mice (O'Hara et al 2011). Moreover, a cohort study of infertile men showed that mutations of AR affect sperm motility and counts in humans (Lazaros et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…AR expression in the developing male genital tract occurs in a strict temporal pattern. It is first detected in the mesenchymal cells, then in the epithelial cells and then in both the epithelial and stromal compartments of the epididymis (Umar et al, 2003;O'Hara et al, 2011).…”
Section: Androgen: Testosterone and Dihydrotestosteronementioning
confidence: 99%
“…In this phase of development, the mesenchymal cells are important androgen targets that elicit androgenic effects in the epithelial cells via paracrine factors and mesenchymal-epithelial interactions (Umar et al, 2003). Genetic mutations in the AR or treatment with AR antagonists during the male embryonic stage results in the regression of the Wolffian ducts and an absence of the epididymis in adult males (O'Hara et al, 2011).…”
Section: Androgen: Testosterone and Dihydrotestosteronementioning
confidence: 99%
See 2 more Smart Citations